Программный комплекс численно-полевых расчётов турбогенератора в режимах холостого хода и нагрузки - Милых, Владимир Иванович; Бадовский, Владимир Александрович (Кременцугский национальный университет им. М. Остроградского, 2009)
A programmatic complex, which built on the basis of the program of numerical calculations of the electromagnetic fields in electric machines, is presented. This numerical calculations is linked with program of services and automation of calculation’s control. The programmatic complex is intended for the calculation of the run idle and the nominal load of turbogenerator
Keywords: режим нагрузки; электромагнитное поле; электрические машины; numerically-field calculation; turbogenerator; run idle; load